Ambiguous Assets for Uncertain Environments: Heterarchy in Postsocialist Firms - David Stark (Journal of Economic Sociology, 2010)
This paper questions the disciplinary division of labor whereby economists study value and sociologists study values; and it rejects the pact whereby economists study the economy and sociologists study the social relations in which economies are embedded. One of the core tasks of economic sociology is to develop a sociology of worth. I explore these themes by discussing the emergence of a new organizational form: heterarchy. Heterarchies are characterized by lateral accountability and the organization of diversity. In them we find an active rivalry of heterogeneous principles of evaluation as actors manuver in multiple networks by attempting to hold resources that are legitimated in more than one regime of worth. Examples of such organizational innovations are drawn from a longitudinal study of the intersecting ownership portfolios of firms in postsocialist Hungary and from my recent research on strategic alliances among new media firms in Manhattan’s Silicon Valley.